Psychometrical of Future Orientation Education Domain Measurement : a Reliability of Future Orientation Questionner - Yanti Rubiyanti; Hendriati Agustiani; Ahmad Gimmy Prathama Siswadi; Ratna Jatnika (Universitas Muhammadiyah Metro, 2021)
To go to life in the future, Seginer (2009) illustrates in the question